Stereotype-forming potential of metaphors in creating the image of Russia in German mass media discourse - V. A. Nagumanova (Дискурс профессиональной коммуникации, 2020)
The paper considers metaphor as a tool of forming and/or maintaining stereotypes about Russia in German mass media discourse. The actualization of stereotypes in media texts plays a key role in creating the image of a country in the mind of the recipient, while researches pay attention to both extralinguistic factors and linguistic ways of introducing a stereotype into the text. Metaphor is one of the effective ways to actualize stereotypes, as it has the ability to influence the perception of information, it can have a strong effect on the recipient, including the formation of his/her world outlook. The author analyzes the implementation of stereotypes about Russia in German mass media through various metaphorical models. The empirical material comprises metaphorical statements selected from online versions of the most popular social and political newspapers and magazines in Germany.